Effects of tetrahydroxystilbene glucoside on mouse liver cytochrome P450 enzyme expressions. (28th October 2014) - Wang, Yan-Ying; Yang, Jun; Liu, Hang; Lin, Feng-Qin; Shi, Jing-Shan; Zhang, Feng
Abstract: 1. To investigate the effects of tetrahydroxystilbene glucoside (TSG), the main active component of Polygonum multiflorum, on mouse liver cytochrome P450 (Cyp) enzyme protein expressions. Male mice were randomly divided into the control, TSG low (10 mg/kg) and high dose (40 mg/kg) groups. After TSG intragastrical administration for 3, 5 and 7 d, mice were sacrificed and the mouse body and liver weight were detected. The Cyp enzymes and various transcription factors such as AhR, PXR and PPARα protein expressions in mouse livers were measured by Western blotting assay. 2. No significant difference of mouse body and liver weight between the control and TSG treatment groups was detected. Additionally, TSG decreased Cyp1a2 and Cyp2e1 protein expressions after TSG treatment for 3, 5 and 7 d, respectively. Moreover, TSG suppressed Cyp3a11 protein expression after TSG treatment for 5 and 7 d. Furthermore, TSG high dose inhibited AhR and PXR protein expressions after TSG treatment for 5 and 7 d, while both TSG low dose and high dose obviously decreased PPARα protein level from TSG treatment for 3 d. 3. TSG has inhibitory effects on mouse liver Cyp1a2, Cyp2e1 and Cyp3a11 protein expressions through the suppression of AhR, PXR and PPARα activation.